2005
DOI: 10.1007/s11095-004-9003-5
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol-Conjugated Copolymers for Plasmid DNA Delivery

Abstract: Polymeric gene delivery systems have been developed as an alternative for viral gene delivery systems to overcome the problems in the use of viral gene carriers. Polymeric carriers have many advantages as gene carriers such as low cytotoxicity, low immunogenicity, moderate transfection efficiency, no size-limit, low cost, and reproducibility. In the efforts to develop safe and efficient polymeric gene carriers, polyethylene glycol (PEG) has widely been used because of its excellent characteristics. PEG-conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
149
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(152 citation statements)
references
References 60 publications
1
149
0
2
Order By: Relevance
“…Such difference might be the result of difference in GFP expression in hUSSCs and hMSCs or size-dependency of nucleic acid transfection in both stem cell types. Altogether it revealed that the nature of the cell itself plays a critical role in effectiveness of transfection as suggested by others (Yamano et al 2010;Lee and Kim 2005).…”
Section: Discussionsupporting
confidence: 54%
“…Such difference might be the result of difference in GFP expression in hUSSCs and hMSCs or size-dependency of nucleic acid transfection in both stem cell types. Altogether it revealed that the nature of the cell itself plays a critical role in effectiveness of transfection as suggested by others (Yamano et al 2010;Lee and Kim 2005).…”
Section: Discussionsupporting
confidence: 54%
“…Finally, PEG-graftment has been successfully used as a spacer moiety between a targeting ligand and a cationic polymer. 21 Moreover, a phase I clinical trial using PEGylated PLL/pDNA complexes has been conducted in cystic fibrosis (CF) patients with some success in partial correction of the CF chloride transport defect, while no inflammatory response or other toxicity due to the gene vector was observed. 33 Nevertheless, an ideal nonviral gene transfer agent has not been identified up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, polyethylene glycosylation (PEGylation) can prevent salt-induced aggregation through steric stabilization [25,26,[29][30][31]33,34]. Additionally, PEG is often used as a spacer for targeting ligands since the shielding effect of PEG is able to decrease nonspecific interactions with negatively charged cellular membranes, which results in reduction of nonspecific cellular uptake [37]. While some PEGylation strategies have had no effect on transfection efficiency in vitro [25,31,33] or in vivo [25], or even enhanced transfection [27,34], others have reported that PEGylation resulted in poor transfection [28,29,32], presumably due to interference with complexation [36].…”
Section: Introductionmentioning
confidence: 99%